Respons Ulama Aceh Terhadap Al-Qur’an Al-Karim dan Terjemahan Bebas Bersajak dalam Bahasa Aceh - Munawir Umar; Yusuf Rahman (Qur'an and Hadith Academic Society, 2020)
This paper analyzes the responses of the Acehnese Ulama to the Al-Qur'an Al-Karim and the Poetic Free Translation in the Aceh language written by Teungku Mahjiddin Jusuf. The methodology used is descriptive-analytical qualitative to describe the response of the Acehnese Ulama using the hermeneutic, anthropological and literary approaches. This study found a variety of responses from Acehnese ulama by concluding as follows. First, from the aspect of sound equality and rhythm, the scholars have given some notes that the translator should pay attention and look for other suitable equivalent words so that they do not affect the distortion of the meaning of the Qur'anic content. Second, in the aspect of fawātiḥ al-Suwar (hurf muqaṭṭa'ah) and the mutasyabihat verse, the scholars agreed with the translation approach used because it was in accordance with the studies of previous scholars with various existing literature.